2008
DOI: 10.1007/s11947-008-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Texture of Pressure-Assisted Thermally Processed Carrots by Combined Pretreatment using Response Surface Methodology

Abstract: The effect of pretreatment pressure (0.1 to 400 MPa), temperature (25 to 75°C), and calcium chloride concentration (0 to 1.5%) and their complex interaction on hardness, residual pectinmethylesterase (PME) activity, and diffused calcium content of pressure-assisted thermal processed (PATP, 700 MPa, 105°C for 15 min) carrot have been studied using response surface methodology. Predicted values of carrot hardness, calcium content, and residual PME activity were found to be in good agreement with experimental val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…Most often, these techniques can compete with conventional heat treatment to reduce microbial populations or improve the nutritional and sensorial properties of food as a raw product (Nguyen, Rastogi, & Balasubramaniam, 2007;Rastogi, Nguyen, Jiang, & Balasubramaniam, 2010;Van der Plancken, Van Loey, & Hendrickx, 2005). Recently, the HHP technique has been used in the enzymatic hydrolysis of proteins to enhance the proteolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Most often, these techniques can compete with conventional heat treatment to reduce microbial populations or improve the nutritional and sensorial properties of food as a raw product (Nguyen, Rastogi, & Balasubramaniam, 2007;Rastogi, Nguyen, Jiang, & Balasubramaniam, 2010;Van der Plancken, Van Loey, & Hendrickx, 2005). Recently, the HHP technique has been used in the enzymatic hydrolysis of proteins to enhance the proteolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The ANOVA for the data obtained using CCRD indicated that the sum of squares due to regression (first and second-order terms) were significant ( Table 4). The high values of coefficient of determination (R 2 , Rastogi et al 2010). …”
Section: Statistical Analysis Of Responsesmentioning
confidence: 99%
“…The contour plots were superimposed (Fig. 3) and the regions that the best satisfied of all the constraints were selected as the optimum conditions and based on that a combination (A, B, C and D) are selected from the shaded area (Table 6) (Rastogi et al 2010;Priyanka et al 2013). Superimposition of contour plots indicated that time 6 min, temperature 101-106°C and absolute pressure 2.51-3.97 kPa fulfilled the above mentioned criteria for optimization.…”
Section: Optimization Of Conditions For Vacuum Fried Beetroot Chipsmentioning
confidence: 99%
“…It also provides comprehensive and informative insight of the system, which leads to process optimization rapidly. The specifications necessary for each response were first set and these also served as constraints for optimization (Floros and Chinnan 1988;Rastogi et al 2009). An acceptable compromise was made following the criteria for the percentage incorporation of n-3 fatty acid ≤18%, ratio of SFA/PUFA ≥0.42, ratio of MUFA/PUFA ≥0.8, and ratio of n-6 to n-3 ≥1.30.…”
Section: Optimizationmentioning
confidence: 99%